Factors Affecting Farmers in Purchasing Grafted Orange Seeds in Tolitoli Regency - Maulana, Lais; Imran, Supriyo; Tolinggi, Wawan; Indriani, Ria; Fajar Haras, Abdul (International Journal of Business and Quality Research, 2025)
Oranges are a horticultural commodity that is high in vitamin C and very easy to cultivate, and because of this, the demand for orange seedlings continues to increase. Grafting is a breeding technique that involves attaching a bud to the bark of a tree in order to obtain the superior characteristics of both indicators. The demand for orange seedlings in Tolitoli Regency is quite high. With the development of the times, the distribution process is not only carried out conventionally but can also be done digitally. Therefore, the purpose of this study is to see the tendency of farmers to purchase grafted orange seedlings digitally and conventionally and the factors that influence it. The method used in this study is Multiple Linear Regression Analysis. The regression analysis results found that the variables of price, convenience, ease of access, and security influence farmers' preferences in purchasing grafted orange seedlings, while the variable of seedling quality does not influence it.